REALIZATION OF FIVE-STAGE CONSTANT CURRENT CHARGING METHOD FOR LI-ION BATTERY CHARGER - Daniel Setiadikarunia; Oh, Braga Geofano Wintora; Sunoto, Tio Dewantho (TESLA: Jurnal Teknik Elektro, 2025)
The demand for high-performance battery systems in electronic devices and electric vehicles has driven the development of faster, more efficient, and safer battery charging methods. The conventional constant current–constant voltage method for charging batteries such as lithium-ion is still widely used because it is easy to implement, but it has limitations in charging speed and the potential for battery degradation due to high initial charging currents and excessive voltage towards the end of charging. This paper presents a novel lithium-ion battery charger design that differs from others based on a five-stage constant current method intended to accelerate charging time and improve charging efficiency. The transition between stages is determined based on the cut-off voltage. The current values for the first and fifth stages are determined, while the current values for the second, third, and fourth stages are obtained through calculation. Experimental results show that the implemented five-stage constant-current charging method battery charger can charge lithium-ion batteries with an average charging efficiency of 90.4%, comparable to battery charger using the constant current-constant voltage method with an average of 90.2%, but with a shorter charging time of almost half, namely an average of 2650.6 seconds for the five-stage constant current charging method and an average of 4480.9 seconds for the constant current-constant voltage method. For the lithium-ion batteries used in the testing, charging the battery with a first-stage charging current of 2.6A and a fifth-stage charging current of 0.125A is the most optimal. ABSTRAK: Kebutuhan terhadap sistem baterai berperforma tinggi pada perangkat-perangkat elektronik sampai kendaraan listrik mendorong pengembangan metode pengisian baterai yang lebih cepat, efisien, dan aman. Metode konvensional constant current–constant voltage untuk mengisi baterai seperti lithium-ion masih banyak digunakan karena mudah diimplementasikan, tetapi memiliki keterbatasan dalam kecepatan pengisian dan adanya potensi degradasi baterai akibat arus awal pengisian yang tinggi dan tegangan yang berlebih menjelang akhir pengisian. Makalah ini menyajikan rancangan pengisi baterai lithium-ion yang baru dan berbeda dari yang lain berbasis arus konstan lima tahap yang ditujukan untuk mempercepat waktu pengisian dan meningkatkan efisiensi pengisian. Transisi antar tahap ditentukan berdasarkan tegangan cut-off. Nilai arus tahap pertama dan kelima ditentukan, sedangkan nilai arus tahap kedua, ketiga, dan keempat diperoleh dari perhitungan. Hasil eksperimen menunjukkan bahwa pengisi baterai dengan metode pengisian arus konstan lima tahap yang direalisasikan mampu mengisi baterai lithium-ion dengan efisiensi pengisian rata-rata 90,4% setara dengan pengisi baterai yang menggunakan metode constant curret-constant voltage rata-rata sebesar 90,2%, tetapi dengan waktu pengisian yang lebih singkat hampir setengah kalinya, yaitu rata-rata 2650,6 detik untuk metode pengisian arus konstan lima tahap dan rata-rata 4480,9 detik untuk metode constant curret-constant voltage. Untuk baterai lithium-ion yang digunakan dalam pengujian, pengisian baterai menggunakan arus pengisian tahap satu 2,6A dan tahap lima 0,125A adalah yang paling optimal.